Evaluasi Sistem Pelaporan Insiden Keselamatan Pasien di Rumah Sakit - Arfella Dara Tristantia (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: Incident reporting systems are designed to obtain information about patient safety and used for organizational and individual learning.Aims: The objective is to evaluate the implementation of patient safety incident reporting system at a hospital of Surabaya.Method: This study was an observational descriptive research supported by qualitative data. This study used Health Metrics Network (HMN) model.Results: The results of the input evaluation show that there was a policy that regulates the incident report, but its implementation was still not appropriate with no direct funding. However, facilities were provided for reporting. There were socialization for employees who have different understanding and responsibility, organizational structure of the patient safety team, problem solving method which had not used PDSA (Plan, Do, Study, Action), and computerized technology.Conclusion: The process evaluation shows that the indicators were in line with the rules. The data sources were in accordance with the guidelines. Data collection, process, presentation, and analysis were in line with the theory. The output evaluation shows the submission of incident reports had not been timely. Moreover, the report was complete and suitable to the existing guidelines, and it had been used for decision-making. It is required for the hospital to revise the guidebook of incidence reporting and improve the human resource skill.Keywords: evaluation, incident, patient safety, reporting